Organize user's manual. - Schwartz, Helen J.; Nachman, Louis J. (Belmont, Calif. Wadsworth Pub. Co., 1987)
An idea-generation and organization program that helps student writers write strong, well-written essays by narrowing and clarifying their topics, deciding on appropriate developmental strategies, and putting together detailed working outlines.
Manual by Helen J. Schwartz and Louis J. Nachman.
Utility disk available on request to publisher.
Issued also in instructor's version with three disks and on-site license and in Apple version.
Keywords: English language -- Rhetoric -- Software; Word processing -- Software